2018
DOI: 10.3390/ijms19092539
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonates: News on Occurrence, Biosynthesis, Metabolism and Action of an Ancient Group of Signaling Compounds

Abstract: Jasmonic acid (JA) and its related derivatives are ubiquitously occurring compounds of land plants acting in numerous stress responses and development. Recent studies on evolution of JA and other oxylipins indicated conserved biosynthesis. JA formation is initiated by oxygenation of α-linolenic acid (α-LeA, 18:3) or 16:3 fatty acid of chloroplast membranes leading to 12-oxo-phytodienoic acid (OPDA) as intermediate compound, but in Marchantia polymorpha and Physcomitrella patens, OPDA and some of its derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
160
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 202 publications
(308 reference statements)
1
160
0
4
Order By: Relevance
“…YFs, young females; Js, juveniles. New Phytologist inactive forms (Wasternack & Strnad, 2018), in nematode-infected roots also correlated with the reduction of bioactive JA-Ile. Upregulation of the SL signaling pathway and suppression of the JA pathway raised the question of whether SLs play a direct role in rice defense against M. graminicola infection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…YFs, young females; Js, juveniles. New Phytologist inactive forms (Wasternack & Strnad, 2018), in nematode-infected roots also correlated with the reduction of bioactive JA-Ile. Upregulation of the SL signaling pathway and suppression of the JA pathway raised the question of whether SLs play a direct role in rice defense against M. graminicola infection.…”
Section: Discussionmentioning
confidence: 86%
“…We also measured defense hormones and found that the jasmonate levels were strongly reduced in nematode‐infected roots. Accumulation of hydroxylated‐ and carboxylated‐JA–Ile, which seem to be inactive forms (Wasternack & Strnad, ), in nematode‐infected roots also correlated with the reduction of bioactive JA–Ile. Upregulation of the SL signaling pathway and suppression of the JA pathway raised the question of whether SLs play a direct role in rice defense against M. graminicola infection.…”
Section: Discussionmentioning
confidence: 97%
“…JA is important for plant defense and reproduction (Wasternack & Strnad, 2018). 5) (reviewed in Wasternack & Strnad, 2018). 5) (reviewed in Wasternack & Strnad, 2018).…”
Section: Biosynthesis Of Phytohormonesmentioning
confidence: 99%
“…Phenotypes of the rice aim1 (abnormal inflorescence meristem 1) mutant in redox gene expression and root development can be rescued by SA treatment, suggesting that rice AIM1whose homolog in Arabidopsis (AtAIM1) is a multifunctional protein (MFP) that is involved in b-oxidationparticipates in SA biosynthesis to regulate ROS concentrations for proper function of the root meristem (Xu et al, 2017). JA is important for plant defense and reproduction (Wasternack & Strnad, 2018). In the octadecanoid pathway for JA biosynthesis, the chloroplast-synthesized JA precursors 12-oxo-phytodienoic acid (OPDA) and dnOPDA are imported into peroxisomes, reduced by OPDA reductase (OPR), and activated to CoA esters that go through the b-oxidation cycles to produce JA ( Fig.…”
Section: Biosynthesis Of Phytohormonesmentioning
confidence: 99%
See 1 more Smart Citation